2000
DOI: 10.1093/ajcn/71.2.514
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vitamin B-12 concentrations relate to intake source in the Framingham Offspring Study

Abstract: In contrast with previous reports, plasma vitamin B-12 concentrations were associated with vitamin B-12 intake. Use of supplements, fortified cereal, and milk appears to protect against lower concentrations. Further research is needed to investigate possible differences in bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
171
6
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(197 citation statements)
references
References 22 publications
14
171
6
4
Order By: Relevance
“…Thus, HO-B12 is a ubiquitous and sometimes predominant form of B12 in food [1]. The daily supply of B12 in a Western omnivorous diet is around 6 µg [3,4], well above the recommended daily allowance (RDA) of 2.4 µg [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HO-B12 is a ubiquitous and sometimes predominant form of B12 in food [1]. The daily supply of B12 in a Western omnivorous diet is around 6 µg [3,4], well above the recommended daily allowance (RDA) of 2.4 µg [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among adults not using vitamin supplements, the relationship between plasma concentration of the vitamin and its intake from dairy products is similar to the relationship observed with the intake from cereals fortified with vitamin B 12 . However, the relationship with intake from meat, poultry or fish is weaker (5) . A Norwegian study showed that plasma vitamin B 12 increases with the amounts of vitamin B 12 provided by dairy products or fish but not with those provided by eggs or meat (6) .…”
mentioning
confidence: 99%
“…This maximum folic acid limit was established because folic acid is known to mask anemia associated with vitamin B 12 deficiency, which are associated with the dose and duration of treatment with folic acid 70 . The non-occurrence of megaloblastic anemia may confuse the diagnosis and irreversible neurological damages may occur due to B 12 deficiency 10,43,70,72,90,91 . Ray et al 92 and Quinlivan et al 93 consider the possibility of adding vitamin B 12 besides folic acid, in cereal fortification programs.…”
mentioning
confidence: 99%